Effects of inlet cavitation on swirling flow in draft-tube cone. Issue 4 (10th July 2018) - Yang, Jing; Hu, Qingjuan; Wang, Zhengwei; Ding, Jinghuan; Jiang, Xianyu
Abstract : Purpose: For Francis turbine, the vortex flow in the draft tube plays an important role in the safe and efficient operating of hydraulic turbine. The swirling flow produced at the blade trailing edge at off-design conditions has been proved to be the fundamental reason of the vortex flow. Exploring the swirling flow variations in the non-cavitation flow and cavitation flow field is an effective way to explain the mechanism of the complex unsteady flow in the draft tube. Design/methodology/approach: The swirling flow in different cavitation evolution stages of varying flow rates was studied. The swirl number, which denotes the strength of the swirling flow, was chosen to systematically analyze the swirling flow changes with the cavitation evolutions. The Zwart–Gerber–Blemari cavitation model and SST turbulence model were used to simulate the two-phase cavitating flow. The finite volume method was used to discrete the equations in the unsteady flow field simulation. The Frozen Rotor Stator scheme was used to transfer the data between the rotor-stator interfaces. The inlet total pressure was set to inlet boundary condition and static pressure was set to outlet boundary condition. Findings: The results prove that the mutual influences exist between the swirling flow and cavitation. The swirling flow was not only affected by the load but also significantly changed with the cavitation development, because the circumferential velocity decrease and axial velocity increase presented with the cavitation evolution. At the high load conditions, the system stability may improve with the decreasing swirling flow strength. Research limitations/implications: Further experimental and simulation studies still need to verify and estimate the reasonability of the swirling flow seen as the cavitation inception signal. Originality/value: One interesting finding is that the swirl number began to change as the inception cavitation appeared. This is meaningful for the cavitation controlling in the Francis turbine.